Neurovascular crosstalk and cerebrovascular alterations: an underestimated therapeutic target in autism spectrum disorders - Wang, Yiran; Yu, Shunyu; Li, Mengqian (Frontiers in Cellular Neuroscience, 2023)
Normal brain development, function, and aging critically depend on unique characteristics of the cerebrovascular system. Growing evidence indicated that cerebrovascular defects can have irreversible effects on the brain, and these defects have been implicated in various neurological disorders, including autism spectrum disorder (ASD). ASD is a neurodevelopmental disorder with heterogeneous clinical manifestations and anatomical changes. While extensive research has focused on the neural abnormalities underlying ASD, the role of brain vasculature in this disorder remains poorly understood. Indeed, the significance of cerebrovascular contributions to ASD has been consistently underestimated. In this work, we discuss the neurovascular crosstalk during embryonic development and highlight recent findings on cerebrovascular alterations in individuals with ASD. We also discuss the potential of vascular-based therapy for ASD. Collectively, these investigations demonstrate that ASD can be considered a neurovascular disease.